DEVELOPMENT OF HUMAN COMPUTER INTERACTION IN THE EDUCATION SECTOR: SYSTEMATIC LITERATURE REVIEW - Novitaningrum, Dian; Khozin, Muhammad; Handayani, Yuni; Hidayat, Taufik (JURNAL TEKNISI, 2025)
Abstract: Rapid technological developments have had a significant impact on various sectors, including education, where Human Computer Interaction (HCI) plays a role in increasing the effectiveness of technology-based learning. However, there are still challenges in the implementation of HCI, such as interface design, infrastructure, and user engagement. This study aims to evaluate the application of HCI in education by reviewing technologies such as chatbots, e-learning, Augmented Reality (AR), Virtual Reality (VR), Artificial Intelligence (AI), and the use of PowerPoint to support learning. Using the Systematic Literature Review (SLR) method based on journals published in 2020-2024 from Google Scholar, the results of the study show that chatbots increase communication efficiency and access to information, while AR and VR-based learning media help understand concepts, especially for students with special needs. The e-learning system designed with HCI principles provides an interactive and user-friendly learning experience, although there are still obstacles such as limited infrastructure and lack of training for educators. In addition, the use of AI in learning media has great potential in increasing engagement and quality of learning. Therefore, this study emphasizes the importance of user-oriented interface design, strengthening technological infrastructure, and collaboration between stakeholders to support more optimal implementation of IMK in the world of education.Keyword: human and computer interaction (HCI); artificial intelligence (AI); augmented reality (AR); education. Abstrak: Perkembangan teknologi yang pesat telah memberikan dampak signifikan di berbagai sektor, termasuk pendidikan, di mana Interaksi Manusia dan Komputer (IMK) berperan dalam meningkatkan efektivitas pembelajaran berbasis teknologi. Namun, masih terdapat tantangan dalam implementasi IMK, seperti desain antarmuka, infrastruktur, dan keterlibatan pengguna. Penelitian ini bertujuan untuk mengevaluasi penerapan IMK dalam pendidikan dengan meninjau teknologi seperti chatbot, e-learning, Augmented Reality (AR), Virtual Reality (VR), Artificial Intelligence (AI), serta penggunaan PowerPoint dalam mendukung pembelajaran. Menggunakan metode Systematic Literature Review (SLR) berdasarkan jurnal terbitan 2020-2024 dari Google Scholar, hasil penelitian menunjukkan bahwa chatbot meningkatkan efisiensi komunikasi dan akses informasi, sementara media pembelajaran berbasis AR dan VR membantu pemahaman konsep, terutama bagi siswa berkebutuhan khusus. Sistem e-learning yang dirancang dengan prinsip IMK memberikan pengalaman belajar yang interaktif dan ramah pengguna, meskipun masih ditemukan kendala seperti keterbatasan infrastruktur dan kurangnya pelatihan bagi tenaga pendidik. Selain itu, pemanfaatan AI dalam media pembelajaran memiliki potensi besar dalam meningkatkan keterlibatan dan kualitas pembelajaran. Oleh karena itu, penelitian ini menekankan pentingnya desain antarmuka yang berorientasi pada pengguna, penguatan infrastruktur teknologi, serta kolaborasi antar pemangku kepentingan guna mendukung implementasi IMK yang lebih optimal dalam dunia pendidikan.Kata kunci: interaksi manusia dan komputer (IMK); artificial intelligence (AI); augmented reality (AR); pendidikan.